Perceived School Bullying Situation in Nepal - Shrestha, Sharmila (NPRC Journal of Multidisciplinary Research, 2025)
This qualitative study explores school bullying experiences in Nepal, focusing on teachers' and students' awareness and understanding at a private school in Kathmandu Valley. Utilizing narrative inquiry, the research unveils challenges and identifies effective strategies to mitigate bullying behaviors. Key findings reveal that teachers' understanding of bullying ranges from recognition of overt acts to a comprehensive grasp of psychosocial impacts, while students' awareness varies widely. The school environment significantly influences bullying prevalence and reporting tendencies, with supportive teacher responses encouraging reporting. Peer dynamics play a crucial role in both perpetuating and combating bullying. The study highlights a disconnect between educational policies and actual practices, exemplified by the principal's endorsement of corporal punishment. Victims report severe emotional turmoil, social ostracization, and physical symptoms. The research concludes that addressing school bullying in Nepal requires a multi-faceted approach considering cultural norms, school climate, and individual perceptions. Implications include developing comprehensive anti-bullying policies, fostering positive school climates, enhancing stakeholder awareness, and implementing culturally appropriate intervention programs. This study calls for a unified approach to create bullying-free school environments and ensure student well-being in Nepal.